the Religious Referral In The Poem Of ‘’monfaridja’’ Of Abi Al-fadl Bin Al-nahwi ( An Interpretive Approach) - mouffok, abdessamiaa (El Omda in Linguistics and Discourse Analysis, 2023)
This study searches in the examination of religious referral aspects in Ibn Al-Nahwi's poem Al-Monfaredja, in which he mixed between the elements of vertical poetic creativity, and the mechanisms of evoking religious heritage in it, in various famous and innovative ways through the poet’s attempt to integrate techniques of expression with thinking during creativity in a verbal cohesion. In order to show that synergy between the elements of creativity in this poem, mechanisms of the interpretive approach were followed that govern the text to previous texts about it by comparison, deduction, citation, discovery and questioning, in order to show those relational ties that link the present text to the absent within the framework of the meaning accepted by the minds and the soul